Comparison of Criteria between Green Building and Non-Green Building Concept - Mohd Rizal, Asmariza; Mohd Asri, Nur Aliesa Azyyati; Rastu Chemerlang, 'Ain Hasanah; Hazirah Bujang,; Mardiha Mokhtar , (Multidisciplinary Applied Research and Innovation, 2023)
Green construction is one of the strategies proposed to lessen the substantial environmental, social, and economic effect of buildings. Sustainable construction is progressively being promoted internationally[1]. However, the development of green buildings is still hampered by a lack of a proper project structure and management. In recent years, environmental conservation is increasingly neglected due to lack of knowledge about the use of green building concepts[2].  If this concept of green development is still underestimated by some communities nowadays, it is not impossible our country will lack animal and plant habitats. So, the objective of this research is to differentiate design and concept of two different buildings. In addition, to classify the characteristic features of green buildings. Finally, analyzing public awareness of green buildings is the final objective of the study.To achieve the objectives of this study, visual inspection and google form were made. This visual inspection involved hospitals namely Jasin Hospital and Sultanah Fatimah Muar Specialist Hospital. Among the things compared between the two hospitals are energy and atmosphere, indoor environment quality, water efficiency, innovation and sustainable sites. Both hospitals were surveyed to obtain data to be analyzed to complete this study. Google form has also been distributed and got 60 respondents.After analyzing the data, improvements need to be made in several aspects. Among the proposed improvements is to build more green buildings in Malaysia. This can to some extent increase public awareness of the importance of knowledge about green buildings because it can provide many benefits in the future.